The Role of Family Communication in Developing Children’s Social Skills - DJEFFAL, Menel; HADDAD, Naceur Eddine (Journal of Ecohumanism, 2026)
This paper aims to elucidate the fundamental role played by the family as a primary sphere of communication and interaction and as a key context for shaping a balanced personality, one that is reflective, socially responsive, and able to engage constructively with both the self and the surrounding environment while also contributing to the development of the wider community. The family furthermore constitutes the social milieu through which the child acquires the capacity to perceive social relationships with others and to act appropriately in social situations. This, in turn, promotes social adjustment and supports a child’s success in future social life.